2018
DOI: 10.1128/mbio.02272-18
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Estrogen Receptor Antagonists for the Treatment of Infectious Disease

Abstract: The concept of repurposing previously approved medications to the treatment of new indications by taking advantage of off-target effects has gained traction in recent years, particularly in areas of medicine that do not offer large profits to pharmaceutical firms. As infectious disease discovery research has declined among large pharmaceutical companies, the potential payoff of repurposing has become attractive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 76 publications
2
47
0
Order By: Relevance
“…In addition, BSAAs showed activity against a wide range of other medically important human pathogens, including fungi, protozoa and parasites (Table S1) (Montoya and Krysan, 2018), pointing out that some pathogens utilize common mechanisms to infect hosts. Moreover, structure-activity relationship analysis of BSAAs suggest that some agents, such as doxycycline, artesunate, omeprazole, nitazoxanide, suramin, azithromycin, minocycline and chloroquine, could have novel antibacterial, antiprotozoal, antifungal or anthelmintic activities (Figure 4).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In addition, BSAAs showed activity against a wide range of other medically important human pathogens, including fungi, protozoa and parasites (Table S1) (Montoya and Krysan, 2018), pointing out that some pathogens utilize common mechanisms to infect hosts. Moreover, structure-activity relationship analysis of BSAAs suggest that some agents, such as doxycycline, artesunate, omeprazole, nitazoxanide, suramin, azithromycin, minocycline and chloroquine, could have novel antibacterial, antiprotozoal, antifungal or anthelmintic activities (Figure 4).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In addition, BSAAs showed activity against a wide range of other medically important human pathogens, including fungi, protozoa and parasites (Table S1) (115), pointing out that some pathogens utilize common mechanisms to infect hosts. Moreover, structure-activity relationship analysis of BSAAs suggest that some agents, such as doxycycline, artesunate, omeprazole, nitazoxanide, suramin, azithromycin, minocycline and chloroquine, could have novel antibacterial, antiprotozoal, antifungal or anthelmintic activities (Fig.…”
Section: Other Activities Of Bsaasmentioning
confidence: 99%
“…20 For repurpose of TAM, antifungal action is another potential activity that can add to its therapeutic ability of breast cancer. 21 Wiseman et al gave the first indicator for antifungal activity of TAM against Saccharomyces cerevisiae. 22 A few years later, many studies demonstrated that TAM has such activity against other types of fungi.…”
Section: Tamoxifen As An Anti-fungal Drugmentioning
confidence: 99%